2019
DOI: 10.1128/aem.01367-19
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Assisted Seamless Genome Editing in Lactobacillus plantarum and Its Application in N -Acetylglucosamine Production

Abstract: Lactobacillus plantarum is a potential starter and health-promoting probiotic bacterium. Effective, precise, and diverse genome editing of Lactobacillus plantarum without introducing exogenous genes or plasmids is of great importance. In this study, CRISPR/Cas9-assisted double-stranded DNA (dsDNA) and single-stranded DNA (ssDNA) recombineering was established in L. plantarum WCFS1 to seamlessly edit the genome, including gene knockouts, insertions, and point mutations. To optimize our editing method, phosphoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Among them, recombinase T (RecT), has been established successfully to enhance the CRISPR-Cas-mediated genome editing in Corynebacterium glutamicum [ 34 ], Lactoccocus lactis [ 35 ], Lactobacillus plantarum , and Lactobacillus brevis [ 36 ]. RecT binds to ssDNA and protects it from degradation, fulfilling a similar function to gamma protein in the lambda Red system [ 37 ].…”
Section: Crispr-cas9-based Methods For Genome Editing In Bacteriamentioning
confidence: 99%
“…Among them, recombinase T (RecT), has been established successfully to enhance the CRISPR-Cas-mediated genome editing in Corynebacterium glutamicum [ 34 ], Lactoccocus lactis [ 35 ], Lactobacillus plantarum , and Lactobacillus brevis [ 36 ]. RecT binds to ssDNA and protects it from degradation, fulfilling a similar function to gamma protein in the lambda Red system [ 37 ].…”
Section: Crispr-cas9-based Methods For Genome Editing In Bacteriamentioning
confidence: 99%
“…This recombinant L. plantarum WCFS1 was able to produce 797.3 mg/L N -acetylglucosamine (GlcNAc) by inducing the GlcNAc pathway. This genetic edition facilitated industrial production of this protein and demonstrated the potential of this genetic engineering technique for application in other organisms ( Zhou et al, 2019 ).…”
Section: Live Bacteria As Mucosal Dna Vaccine Delivery Systems: mentioning
confidence: 96%
“… Zhou et al (2019) , in an attempt to increase protein production without inserting exogenous genes, used CRISPR/Cas9 to engineer L. plantarum strain WCFS1 to produce N-acetylglucosamine (GlcNAc). This was achieved by truncating the gene nag B, which eliminates the reversion of fructose-6-phosphate (F6P) back to glucosamine-6P.…”
Section: Live Bacteria As Mucosal Dna Vaccine Delivery Systems: mentioning
confidence: 99%
“…The plasmid system developed here could potentially be transportable to other Gram-positive bacteria, as the used origin of replication was shown to be functional in Lactococcus lactis and Bacillus subtilis ( 20 ). While similar approaches have recently been undertaken to perform genome engineering in certain Gram-positive organisms such as Enterococcus faecium ( 21 ), Clostridium ( 22 ), Lactobacillus reuteri ( 23 ), Lactobacillus plantarum ( 24 ), and Lactococcus lactis ( 25 ), a concise CRISPR sgRNA:Cas9 gene editing system was not yet available for S. pneumoniae , and the vector described here has the advantage of being readily curable due to its temperature-sensitive origin of replication.…”
Section: Introductionmentioning
confidence: 99%